2018
DOI: 10.1039/c8ee01348a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis cost dictates the commercial viability of lead sulfide and perovskite quantum dot photovoltaics

Abstract: Any new solar photovoltaic (PV) technology must reach low production costs to compete with today's marketleading crystalline silicon and commercial thin-film PV technologies. Colloidal quantum dots (QDs) could open up new applications by enabling lightweight and flexible PV modules. However, the cost of synthesizing nanocrystals at the large scale needed for PV module production has not previously been investigated. Based on our experience with commercial QD scale-up, we develop a Monte Carlo model to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
120
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 29 publications
2
120
0
Order By: Relevance
“…In a separate synthetic step, OAcapped PbS QDs are exchanged with short ligands in solution and then suspended at a high concentration in a solvent to form an ink. [8] In addition to this added cost, the toxicological properties, environmental impact, and end-of-life disposal of Pb-based PVs, including perovskites, is of critical importance and has received only minimal attention. [1] With this advancement the fabrication of the active layer is now more facile, however, the scalability of PbS QD solar cells is still uncertain.…”
mentioning
confidence: 99%
“…In a separate synthetic step, OAcapped PbS QDs are exchanged with short ligands in solution and then suspended at a high concentration in a solvent to form an ink. [8] In addition to this added cost, the toxicological properties, environmental impact, and end-of-life disposal of Pb-based PVs, including perovskites, is of critical importance and has received only minimal attention. [1] With this advancement the fabrication of the active layer is now more facile, however, the scalability of PbS QD solar cells is still uncertain.…”
mentioning
confidence: 99%
“…Finally, large‐scale and cost‐efficient production of robust QDs with precisely controlled optical properties, high photo and thermal stability, preprogrammed chemical compositions, and long shell life can catalyze fast future progress. This acceleration has already happened very recently in a wide range of general commercial applications, such as in the field of large TV and large panel displays with enhanced brightness and colored characteristics due to the embedded QD‐containing light sources and multicolored pixels …”
Section: Qd Composite Structure For Lasingmentioning
confidence: 99%
“…The research group of Vladimir Bulović of the Massachusetts Institute of Technology finds that this approach of focusing solely on PCE might not be the most favorable route to commercialization of this technology. 5 They found that the CQD synthesis step currently limits production costs. They also found that the currently used hot-injection synthesis method is significantly capital-intensive, owing to low yields and therefore incompatible with industrial scale-up.…”
mentioning
confidence: 99%
“…6 The heat-up method allows for high yields resulting in reduced synthesis costs down to USD$0.15/W from USD$0.51/W for the hot-injection method (compared to <USD$0.4/W for commercial silicon PV). 5 Additional encapsulant layers and balance-ofmodule components required for CQD PV, however, expectedly increase this number significantly. Jean et al 5 present guidelines to reduce CQD synthesis costs to as low as USD$0.05/W, including avoiding expensive precursors, deploying lowergrade precursors, and recycling solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation